Development of a Berry Processing Score for Sorghum Silage - J. R. Johnson; J. P. Goeser; Michael Brouk (Kansas Agricultural Experiment Station Research Reports, 2016)
This study was done in an effort to develop a berry processing score (BPS) for sorghum silage, similar to the kernel processing score (KPS) currently used for corn silage. Sorghum silage samples were collected from 3 dairies in Kansas and processed in the Grain Science & Industry grain processing laboratory at Kansas State University using one of four different roll gap settings to give four differently processed samples: unprocessed, 1.5, 1.0, or 0.5 mm. After drying, samples were placed into a Ro-Tap particle separation machine for 10 minutes until the whole sample was separated. Whole samples, as well as separated fiber and whole berry portions were analyzed for percent starch retained on each screen. As the roll gap was reduced, mean particle size (MPS) was also reduced. Percent starch passing through the 1.7 mm screen was greater at the 0.5 mm roll gap for both the whole sample and the whole berry samples, indicating successful processing of the samples. Using these data, we have determined that the appropriate screen to use in determining a BPS for sorghum silage is the 1.7 mm screen. A BPS for any sorghum silage sample can be calculated by analyzing the whole sample for the percent starch that passes through the 1.7 mm screen. This study is still ongoing and more research is needed to determine the recommended BPS in sorghum silage.
Keywords: milo; sorghum; dairy cattle; feed; processing; silage